Manajemen Sekolah Dalam Meningkatkan Mutu Sekolah - M Rudi Gunawan Parozak; Fadma Rosita (JURNAL ASIMILASI PENDIDIKAN, 2025)
The purpose of this study is to examine the implementation of school management in improving school quality, and to examine the planning and implementation of school programs in an effort to improve school quality. The research method is a descriptive method. This research was conducted at MI Nurussyifa Timbanuh, East Lombok. The data sources for this study were the principal and teachers. Data collection techniques in descriptive research are documents, archive recordings, interviews, direct observation, participant observation, and physical devices. The data analysis technique used in formulating the problem analysis is an interactive technique. The results of the research that has been conducted are as follows: school management has been carried out by the school by carrying out a management process based on the scope of curriculum management, financial management, personnel management, and management of facilities and infrastructure. The results of the study indicate that school management has been carried out well, but has not used the right method to obtain maximum results, so that improvements can be made. Evaluation has also not been carried out optimally. There needs to be an evaluation of the learning process and synchronization in an effort to improve school quality. An evaluation of human resources needs to be carried out at least twice a year or at the end of each semester. Evaluation of student learning outcomes also needs to be carried out.